Study of in-plane Fatigue Failure and Life Prediction of Weave Composites under Constant and Variable Amplitude Loading. Issue 8 (October 2016) - Ji, Qinghui; Zhu, Ping; Lu, Jiahai; Liu, Zhao
The fatigue behaviour of two-dimensional weave composites under constant and variable amplitude loading was discussed in this article. The theories of life prediction methods were represented, including cycle counting, S–N formulation, constant life diagrams (CLD), damage accumulation rule and stress analysis. Special focuses on CLDs were studied through the interpolation method known as the kriging model. Fatigue tests under constant amplitude loading were carried out utilising the servo-hydraulic Shimadzu testing machine. Tension–tension, tension–compression and compression–compression loading patterns were investigated in fatigue testing. The macro-failure mode was obviously different between tensile and compressive loading. Micro-failure surfaces were observed in micro-mechanism with scanning electron microscopy (SEM). The Basquin equation and the linear Palmgren–Miner (P–M) rule were employed to characterize the fatigue properties under random loading conditions. A new constitutive relation was introduced which took into account the tensile-compressive asymmetry of composites. Finally, the benchmarking for the stochastic loading case was executed using proposed methodology and variable amplitude fatigue experiments. Through the contrast between prediction and the experimental data, it was inferred that the proposed prediction method under any loading conditions (stress ratios and ranges) gave an accurate life prediction.